TEACHER’S VOICE. TEACHER’S TONE IN THE CLASSROOM - Ermatova Dilafruz Yodgorjon qizi; Qodirova Nurxon Yusufjon qizi (Ustozlar uchun, 2023)
Annotation: Why is a teacher’s tone of voice such an important part of their job? Simply put, your tone of voice as a teacher helps establish authority, create a structured learning environment, and set the tone for the class in terms of behaviour, engagement and even your rapport with your students. A teacher must know how to strike the right balance to be seen as authoritative, but not unapproachable or intimidating. You need to show you are in charge, while still being able to give genuine praise and encouragement. There are a few important things to keep in mind to strike the right balance.